2017
DOI: 10.4018/ijegr.2017070104
|View full text |Cite
|
Sign up to set email alerts
|

Use of Social Media in Citizen-Centric Electronic Government Services

Abstract: This article undertakes a literature review on such articles on social media and citizen-centric e-government services. This research uses 139 articles to perform the intended literature review. The keywords analysis of these articles indicates that Web 2.0, participation and open government/open data were some of the frequently used keywords in addition to the two major themes of e-government and social media on which all the articles were searched for. The analysis of research methods indicated that majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 106 publications
1
27
0
Order By: Relevance
“…Recent advances in social technologies are transforming government-citizen interactions (Alryalat, Rana, Sahu, Dwivedi, & Tajvidi, 2017;Rana, Dwivedi, & Williams, 2015). With a current base of more than 2 billion users, social media platforms have become major catalysts in changing how the government interacts with its constituents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in social technologies are transforming government-citizen interactions (Alryalat, Rana, Sahu, Dwivedi, & Tajvidi, 2017;Rana, Dwivedi, & Williams, 2015). With a current base of more than 2 billion users, social media platforms have become major catalysts in changing how the government interacts with its constituents.…”
Section: Introductionmentioning
confidence: 99%
“…However, diverse obstacles have hindered such attempts. Some recent reviews (Alryalat, et al, 2017) have declared that published research on this topic is problematic due to "a lack of theory-based research in the area" (p. 55). Other reviews (Boulianne, 2015;Estevez & Janowski, 2013;Kapoor et al, 2018;Skoric, Zhu, Goh, & Pang, 2016) have indicated that most relevant studies merely present broad discussions on interactions between the government and the general public.…”
Section: Introductionmentioning
confidence: 99%
“…A range of online communication channels, including interpersonal communication (e.g., Twitter, Facebook), content communities (e.g., Wikipedia) and multimedia platforms (e.g., YouTube, Instagram), offer individuals and businesses the ability to connect, develop and maintain social and business relationships through the exchange of ideas and opinions (e.g., Alalwan et al 2017;Alryalat et al 2017;Ellison and Boyd 2013;Ellison et al 2007;Filieri et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Consumers have become increasingly empowered to exert an influence on brands through online communities, while businesses are able to acquire rapid feedback and garner insight into individual preferences without observer effects (AlAlwan et al 2017;Ismagilova et al 2017;Kapoor et al 2016;Plume et al 2016) and use such data for new product development (Rathore et al 2016). Social media tools also enable citizens to share advice and information with their local community (Oh et al, 2013), from promoting events to searching for lost pets, and aids government engagement with citizens (Alryalat et al 2017).…”
mentioning
confidence: 99%